Kesadaran Umat Muslim Dan Informasi Boikot Produk Terhadap Perilaku Pembelian Melalui Niat Pembelian - Margarena, Agung Novianto; Setiawan, Setiawan; Fauzi, Irsal; Aziz, Abdul; Auliya, Zakky Fahma (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This research aims to find out whether the Israeli and Palestinian wars influence Millennial Muslim purchasing behavior towards pro-Israel products. The large amount of information calling for a boycott of pro-Israel products which is currently popular in Indonesia is the basis for this research. The Theory of Reasoned Action (TRA) construct is used as an analytical framework involving awareness variables, information about product boycotts, purchase intentions, and purchase behavior. This research is classified as quantitative descriptive research with a sampling technique using random sampling of 114 millennial respondents in the city of Salatiga, Indonesia. The analytical tool in this research uses SEM AMOS ver. 21 with instrument tests, normality tests, singularity multicollinearity tests, model feasibility tests, and hypothesis tests. The research results show that awareness as a Muslim and information about product boycotts have a significant effect on purchasing behavior through the intention to purchase pro-Israel products among millennial Muslims. The findings of this research are that collective culture as a Muslim plays a big role in the intention and behavior of boycotting the purchase of pro-Israel products.The recommendation of this research is the need for local substitute products to emerge Keywords: Theory of reasoned action, Muslim awareness, information about product boycott, purchase intention, behavior